Maternal and neonatal outcomes following a prolonged second stage of labor: A meta-analysis of observational studies. (September 2020) - Pergialiotis, Vasilios; Bellos, Ioannis; Antsaklis, Aris; Papapanagiotou, Angeliki; Loutradis, Dimitrios; Daskalakis, George
Abstract: Several articles investigated the impact of prolonged second stage of labor on maternal and neonatal outcomes; however, strict consensus is still lacking. The purpose of the present meta-analysis is to investigate risk factors that contribute to the pathophysiology of prolonged labor as well as effect sizes of maternal and neonatal morbidity. We searched Medline, Scopus, Clinicaltrials.gov, EMBASE, Cochrane Central Register of Controlled Trials CENTRAL and Google Scholar database. Observational studies (prospective and retrospective) were considered eligible for inclusion in the present meta-analysis. To minimize the possibility of article losses we avoided language, country and date restrictions. Meta-analysis was performed with the RevMan 5.3 and secondary analysis with Rstudio. Overall, 13 studies were included in the present systematic review that comprised 337.845 parturient. Prolonged second stage was associated with higher odds of postpartum hemorrhage, chorioamnionitis, endometritis, postpartum fever and obstetric anal sphincter injury. Persistent occiput posterior position and shoulder dystocia were also more prevalent compared to women with normal duration of the second stage. The need for admission to the neonatal intensive care unit was higher as well as the risk of developing neonatal sepsis. On the other hand, the odds of perinatal death were comparable among cases with prolonged and normal duration of the second stage. The results of the present meta-analysis clearly indicate that deliveries following a prolonged second stage of labor are at increased risk of maternal and neonatal complications. The presented effect estimates can be used in current clinical practice during patient counseling.